Traffic condition awareness using kalman filter technique with the aid of arduino and matlab embedded system author - Azad, Dr. A.K.M Abdul Malek (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.